Ocena vala P300 pri bolnikih s Parkinsonovo boleznijo - Pišljar, Marko (Zdravniški vestnik, 2001)
Background. Mild to moderate cognitive dysfunction is a frequent complaint of patients with Parkinson's disease, though the clinical picture of dementia is rarely reported. Methods. The development of cognitive deficits seams to be associated with hypokinesia and rigidy rather than tremor. In our study, auditory ERP were used to confirm cognitive alterations in two groups of non-dementedpatients with idiopathic Parkinson's disease. Mini mental test wasperformed to exclude clinical picture of dementia. Patients were classifiedaccording to the Hoehen-Yahr and Webster scale. The Beck depression score in Parkinson's patient was assessed. Auditory event related potentials were recorded using the "oddball" paradigm. The waves N100, P200, N200 and P300 were recorded and their latencies and amplitudes measured Results and conclusions. The P300 latencies in both patients group were significantly longer (p < 0.05), than in the control group. P300 latency was longer in non tremor group. There were no significant statistical differences in latencies between the both groups. All patients had normal N100 latency. Significant decline of P300 amplitude was found only in non-tremor group (p < 0.001).
Keywords: bolniki; Cognition disorders; Dogodek-povezani potenciali, P300; Event-related potentials, p300; Parkinson disease; Parkinsonova bolezen; Spoznava, motnje; spoznavne funkcije